Peningkatan Hasil Belajar Bahasa Jawa Materi Menulis Karangan Cerita Peristiwa Alam dengan Media Power Point pada Siswa Kelas V SD - Purwati Purwati (Universitas Sebelas Maret, 2019)
AbstractThe research is based on the students difficulties in writing stories. The research aims to determine if the Power Point media can improve the learning outcomes of grade V students on Javanese language subjects. This research is classroom action research with qualitative and quantitative descriptive approaches. The research uses two cycles. Each cycle consists of planning, implementation, observation and reflection phases. The data collection techniques use observation, tests and documentation. The research subjects are 19 students of fifth grade at SDN Sugiharjo 02 Pati. In the first cycle, the learning mastery is 63.16% or two students fail with score 74.21. In the second cycle, 100% of students pass the learning mastery with an average score 78.68. It concludes that Power Point can improve the learning outcomes of fifth grade students of SDN Sugiharjo 02 Pati in the subject of Javanese language especially in writing essay about natural phenomenon in the second semester of academic year 2017/2018.Keywords: writing essay, Power Point, learning outcomes, Javanese languageAbstrakPenelitian ini didasarkan pada kesulitan siswa menuliskan cerita. Penelitian ini bertujuan untuk mengetahui apakah media Power Point dapat meningkatkan hasil belajar siswa kelas V pada mata pelajaran bahasa Jawa menulis cerita. Jenis penelitian tindakan kelas dengan pendekatan deskriptif kualitatif dan kuantitatif.Penelitian ini menggunakan dua siklus, setiap siklus terdiri dari tahap perencanaan, implementasi, observasi dan refleksi.Teknik pengumpulan data penelitian ini menggunakan teknik observasi, tes dan dokumentasi. subjek penelitian adalah 19 siswa kelas V SDN Sugiharjo 02 Pati. Pada siklus I ketuntasan hasil belajar siswa sebesar 63,16% atau 2 tidak tuntas dengan nilai 74,21. Pada siklus II 100% siswa tuntas dengan nilai rata-rata 78,68. Kesimpulan penelitian ini Power Point dapat meningkatkan hasil belajar siswa kelas V SDN Sugiharjo 02 Pati pada mata pelajaran bahasa jawa materi menulis karangan cerita tentang peristiwa alam semester 2 tahun pelajaran 2017/2018.Kata Kunci: menulis karangan, power point,hasil belajar, bahasa jawa